PENGEMBANGAN MEDIA KARTU KATA BERGAMBAR UNTUK KETERAMPILAN MEMBACA PERMULAAN PADA PESERTA KELAS 1 SDN 05 PULAU PUNJUNG - Yulia Darniyanti; Anggrayni; Tati Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the problem of students who have not memorized letters, and distinguishing between letters that have the same shape, students still have difficulty spelling letters and are also less fluent in reading. The aim of this research is to produce picture word card learning media that is valid, practical and effective. The type of research used is development research or Research and Development (R&D) using the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation stage ( evaluation). The results of the validity of the picture word card media were validated by 3 validators, namely material expert validation obtained a result of 92.5% categorized as very valid, language expert validation obtained a result of 93.75% categorized as very valid, media expert validation obtained a result of 90% categorized as very valid, validation The teaching module obtained a result of 93.33% categorized as very valid, validation of the teaching module by the teacher obtained a result of 100% categorized as very valid. The results of the practicality of the picture word card media through the teacher response questionnaire by class 1 teachers obtained a result of 100% categorized as very practical, while through the student response questionnaire an average result of 96.27% was categorized as very practical. The effectiveness results obtained from the learning test results of primary school students obtained an average of 89.47%, categorized as very effective.